Food Security Education Through The “Love to Plant From an Early Age” Program : Implementing A Vegetable Garden in Schools - Caroline B. D. Pakasi; Noortje M. Benui (Yayasan Bina Lentera Insan, 2025)
The partners in this Community Partnership Program are elementary schools consisting of students, teachers, staff, and parents at GMIM 30 Elementary School in Sario Tumpaan Subdistrict, Sario District. The partner, GMIM 30 Sario Tumpaan Elementary School, as the target audience of the PKM program, represents a group of young community members who are the intended beneficiaries. Understanding the concepts and implementation of food security and food availability requires educational efforts from an early age, including through the application of the “love to plant” concept for elementary school students — the next generation who will face various challenges related to environmental sustainability and food security. By introducing them to planting activities early on, they will better understand how food is produced, the importance of protecting the environment, and develop an awareness to live healthily and independently. The problem is that implementing education to raise early awareness of planting among school children and practicing vegetable gardening at school faces several challenges, namely the absence of human resources at the school who can serve as educational facilitators and provide technical assistance in creating the garden. Additionally, students and teachers need to be motivated to participate in these activities so that the program can be carried out in accordance with its goals of promoting food security starting from elementary school. The solution to be implemented at the elementary school is collaboration with lecturers from the Faculty of Agriculture at Sam Ratulangi University to provide education to the students so that from an early age they can be taught about food security and the love of planting. In addition, there will be hands-on practice in planting vegetables and creating a vegetable garden at the school to encourage students to engage and develop an interest in agriculture as a food provider in support of the Food Security program.